Blood eosinophils and inhaled corticosteroids in patients with COPD: systematic review and meta-analysis - Cheng, Shih-Lung (Int J Chron Obstruct Pulmon Dis, 2018)
BACKGROUND: COPD is a highly heterogeneous disease. Potential biomarkers to identify patients with COPD who will derive the greatest benefit from inhaled corticosteroid (ICS) treatment are needed. Blood eosinophil count can serve as a predictive biomarker for the efficacy of ICS treatment. The aim of this systematic review and meta-analysis was to assess whether a blood eosinophil count of ≥2% in patients undergoing ICS therapy was associated with a greater reduction in COPD exacerbation rate and pneumonia incidence. MATERIALS AND METHODS: An electronic search was performed using the keywords “COPD”, “eosinophil”, and “clinical trial” in the PubMed and EMBASE databases to retrieve articles, up to 2017, relevant to our focus. Data were extracted, and a meta-analysis was conducted using RevMan 5 (version 5.3.5). RESULTS: Five studies comprising 12,496 patients with moderate-to-very severe COPD were included. At baseline, 60% of the patients had ≥2% blood eosinophils. Our meta-analysis showed a 17% reduction in exacerbation of moderate/severe COPD in patients with ≥2% blood eosinophils undergoing ICS therapy compared to the non-ICS/ICS withdrawal/placebo group. The difference between the two types of treatment was significant (risk ratio [RR], 0.816; 95% CI, 0.67–0.99; P=0.03). Furthermore, the risk of pneumonia-related events was significantly increased in the subgroup with eosinophil count ≥2% undergoing ICS-containing treatments (RR, 1.969; 95% CI, 1.369–2.833; P<0.001). There was no significant difference in the subgroup with eosinophil count <2% (RR, 1.29; 95% CI, 0.888–1.879; P<0.181). CONCLUSION: The results of our meta-analysis suggest that the 2% threshold for blood eosinophils could accurately predict ICS treatment response in patients with COPD, but increased the risk of pneumonia.